Pain patterns during adolescence can be grouped into four pain classes with distinct profiles: A study on a population based cohort of 2953 adolescents. (27th December 2017) - Holden, S.; Rathleff, M.S.; Roos, E.M.; Jensen, M.B.; Pourbordbari, N.; Graven‐Nielsen, T.
Abstract: Introduction: Although multi‐site pain is common in adolescents, pain conditions are frequently diagnosed and treated in isolation. Little is known about whether there are specific sites in which pain commonly co‐occurs. This study examines the patterns of pain in adolescents, and whether these are associated with sports participation, health‐related quality of life (HRQoL), and sex. Methods: In previously collected cohort data ('Adolescent Pain in Aalborg‐2011'), adolescents (aged 12–19) completed an online questionnaire, including demographic data, current pain sites, sports participation and HRQoL (assessed by Euro‐QoL 5D‐3L). Latent class analysis was used to classify spatial pain patterns, based on the pain sites. The analysis included 2953 adolescents. Results: Four classes were identified as follows: (1) little or no pain (63% of adolescents), (2) majority lower extremity pain (10%), (3) multi‐site bodily pain (22%) and (4) head and stomach pain (3%). The lower extremity multi‐site pain group reported highest weekly sports participation ( p < 0.001; mean: 2.9 days/week; 95% CI 2.7 to 3.2), while the multi‐site bodily pain and the multi‐site head and stomach pain groups had lowest EQ‐5D scores ( p < 0.001). Males were more likely to belong to the little or no pain class, whereas females were more likely to belong to the multi‐site bodily pain class. Conclusions: Latent class analysis identified distinct classes of pain patterns in adolescents, characterized by sex, differences in HRQoL and sports participation. The class with multi‐site bodily pain and reduced quality of life was the largest among adolescents reporting pain, and future research on treatment strategies should consider targeting this group.